A new automated motion planning system of heavy accelerating articulated vehicle in a real road traffic scenario. (March 2020) - Shojaei, Saeed; Hanzaki, Ali R; Azadi, Shahram; Saeedi, Mohammad A
The main purpose of this study is to develop a novel motion planning for an articulated vehicle (AV) in real traffic situations. This motion planning generates collision-free and feasible trajectories based on kinematic and dynamic analyses of the AV concerning its surrounding vehicles. For this purpose, the collision-free trajectories are simulated in the presence of other vehicles, when the AV is conducting a lane change manoeuvre. A new method is utilised to derive the feasible trajectories by taking into account 3-D surface of the slip angle, roll angle, and lateral acceleration of the AV. This paper presents a new approach to generate the trajectory of an accelerating AV considering the surrounding vehicles in manoeuvre, which are either accelerating or decelerating. The optimal trajectory is then obtained based on the longitudinal acceleration of the AV and the time duration of the lane change manoeuvre, aimed at trajectory tracking control. Therefore, a 3-DOF dynamic model of the AV, including the yaw-rate, lateral velocity of the tractor and articulation angle, is developed. The tyres dynamic is simulated using non-linear Dug-off model. Furthermore, an innovative trajectory tracking control system is proposed concerning a sliding mode control. The developed dynamic model of the AV is verified by the Truck-Sim model. Results show that the collision-free and feasible trajectories can be generated based on the newly presented method of trajectory planning. The outcomes of the trajectory tracking control as the final part of the motion planning system indicate that the heavy articulated vehicle can be guided according to the new automated motion planning.